A clinical comparative study to Evaluate soft liners’ efficacy as final impression material in the retention of upper complete dentures’ bases - احمد, محمود; محمود محمود , (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: One of the most important and difficult challenges facing the prosthetist is complete denture's stability, which is provided by good fit in the final impression stage. Aim: This study aims to evaluate upper complete dentures bases' retention when using soft lining materials as final impression material in comparison with the traditional materials. Materials and Methods: Ten completely upper edentulous patients were selected to evaluate the retention of acrylic denture bases provided by three different final impression techniques (The first impression was recorded using low-fusion compound as border molding and light body of PVS as final impression, the second impression was recorded using low-fusion compound as border molding and zinc oxide-eugenol paste as final impression, and the third impression was recorded by single step technique using direct soft lining materials as border molding and final impression). Results: Statistical analysis results showed that there were no differences in upper complete dentures bases' retention between the three used techniques. Conclusions: The single-step recording technique (border molding + final impression) using acrylic direct soft lining material provided similar clinical retention on dentures' bases compared to the traditional two-step technique.